Status fotografij kot knjižničnega gradiva in njihova katalogizacija v perspektivi slovenskih priročnikov, pravilnikov in standardov - Kerec, Branka (Knjižnica, 2004)
The article presents an overview of Slovene handbooks, regulations and standards, which are, or have been, used in the cataloguing of library materials. The research is concentrated on their relation with photographic materials ie. with the smallest part, the photograph. The status of photographs is being looked at in the first Slovene handbook Knjižnice in knjižničarsko delo, the first Slovene regulations Abecedno imenski katalog andits second edition, and in Pravilnik i priručnik za izradbu abecednih kataloga (PPIAK). The International Standard Bibliographical Description for Non-Book Materials (ISBD(NBM)) and PREKAT also deal with the cataloguing of photographs. Greater attention is paid to the Pravila za katalogizacijo v grafičnih zbirkah, which is the work of professional committees of the Union of Associations of Slovene Librarians. Although some of the regulations are quite old, they are still very practical and usable. The author examines the handbooks from the point of view of how detailed and accurately they provide the regulations for cataloguing photographs.
Keywords: neknjižno gradivo; fotografsko gradivo; fotografije; posebne zbirke; katalogizacija; pravilniki; standardi